Fabrication and characterisation of polytetrafluoroethylene-borosilicate and polytetrafluoroethylene-soda lime silica glass composites for microwave substrate application - Alhaji, Ibrahim Abubakar (2022)
Rapid and unprecedented developments in the information technology and telecommunication industry demands high-speed, light and low-cost microwave substrates for high-frequency applications. This work presents the preparation of low-cost composites using borosilicate (BRS) and soda lime silicate (SLS) glasses. The glasses were used as fillers in the polytetrafluoroethylene (PTFE) matrix as a replacement for woven fiberglass and ceramics to reduce the cost and improve the performance of PTFE-based composites for microwave substrate application. The BRS and SLS glass powders were recycled using glass waste through ball milling. The dependence of the complex permittivity on BRS and SLS grain sizes was determined. A 63 μm grain size fillers were selected to fill the PTFE matrix through a dry powder processing technique. Surface morphology and material composition were analysed using X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray (EDX). Tensile strength, coefficient of thermal expansion (CTE), density,and moisture absorption of the composites were studied with respect to filler sizeand content. The dielectric properties were characterised from 8 GHz to 12 GHz for a rectangular waveguide (RWG) and from 1 GHz to 12 GHz for an open-ended coaxial probe (OCP). In addition, the characterisation was conducted at room temperature using a vector network analyser. Similarly, the RWG was used to measure the magnitude of reflection (|S11|) and transmission (|S21|) coefficients. The results of the OCP and RWG methods indicated that the dielectric properties of all composites increased with filler content, however, the RWG method exhibited higher values than the OCP method due to the presence of air gaps in the latter method. At 10 GHz frequency, the dielectric constant (ε'), loss factor (ε'') and loss tangent (tanδ) of PTFE/BRS and PTFE/SLS composites varied from 2.11, 0.0022, 0.0011 and 2.11, 0.0022, 0.0011 to 2.24, 0.0029, 0.0013 and 2.57, 0.0031, 0.0012, respectively, for the OCP method. For the RWG method, the ε', ε'', and tanδ had a respective change from 2.16, 0.0035, 0.0015, and 2.18, 0.0035, 0.0016 to 2.31, 0.0042, 0.0018 and 2.57, 0.0047, 0.0018 when filler content was varied from 5 wt.% to 25 wt.%. In addition, the results of |S11| and |S21| were used to calculate the power loss (dB) for the different volume fractions of PTFE/BRS and PTFE/SLS composites. The power loss at 10 GHz frequency was found to be from 3.33 dB and 3.48 dB to 3.89 dB and 3.85 dB in that order. Furthermore, the electric field distribution through the dielectric composites in the RWG was visualised for various filler content and then used to calculate the attenuation of the electric field intensity. The attenuation was found to increase from 3.67 dB and 3.70 dB to 3.81 dB and 3.77 dB for the PTFE/BRS and PTFE/SLS composites, respectively, when the filler content was adjusted from 5 wt.% to 25 wt.%.